Avaliação de tuberculose latente em adolescentes e adultos jovens vivendo com o vírus da imunodeficiência humana em um serviço de referência no Brasil - Fernanda Maia Brustoloni; Fabiana Bononi do Carmo; Aida de Fátima Thomé Barbosa Gouvêa; Regina Célia de Menezes Succi; Daisy Maria Machado (Sociedade Brasileira de Pediatria, 2023)
To avoid the occurrence of tuberculosis reactivation in people living with HIV (PLHIV) who have latent tuberculosis infection (LTBI), the therapeutical indications to this population were expanded in Brazil in 2018, with the recommendation of treatment for those with CD4 T lymphocyte count less than or equal to 350 cells/mm3, regardless of the result of the tuberculin test (TT). To evaluate the practical application of this recommendation, we decided to determine the prevalence of LTBI in PLHIV followed in our outpatient clinic. Ninety-nine adolescents and young adults living with HIV accompanied in a Reference Service were evaluated for the occurrence of LTBI with TT and TCD4 cell count application. The prevalence of LTBI was estimated at 7.1% considering the result of TT, and 18% when considering patients with CD4 lymphocyte count less than or equal to 350 cells/mm3. This difference reinforces the idea that the detection of patients with TCD4 lymphocytes less than or equal to 350 cells/mm3 effectively expands the indication for treatment of LTBI. However, only 4 (22.2%) of 18 patients with TCD4 less than or equal to 350 cells/mm3 adhered to the therapeutic proposal. The rebellious aspect inherent to this population, the failure to attend consultations and the refusal to use another drug were some of the reasons for the low adherence to treatment.